Nonsteroidal Anti-Inflammatory Drugs - Gamal Ahmed Al-kaf, Ali (IntechOpen, 2017)
This book intends to provide the reader with a comprehensive overview about the state of the art regarding the use of nonsteroidal anti-inflammatory drugs (NSAIDs) in physical and rehabilitation medicine and the study of the pharmacodynamics of existing and newly introduced NSAIDs in the management of pain and inflammation. It will also elaborate and refine already known knowledge on the mechanism(s) of nonsteroidal anti-inflammatory agents. This book may provide additional knowledge about the design and development of new drug delivery systems loaded with NSAIDs potentially useful in the treatment of chronic inflammatory-based diseases following circadian cycle, uses of NSAIDs as a source of medicinal plants, and the adverse effects and drug interactions of the nonsteroidal anti-inflammatory drugs.